First principles calculations to probe electronic response of lithium tetraborate. (March 2020) - Jangid, Pawan K; Arora, Gunjan; Mali, Deepika; Joshi, P K; Kumar, Kishor; Ahuja, B L
Abstract: Electronic structure of thermoluminescent (TL) lithium tetraborate (Li2 B4 O7 ) using density functional theory is presented. We have computed the E-k relations and density of states (DOS) by applying ab-initio LCAO and FP-LAPW theories. The band gaps obtained using local density approximation (LDA) within LCAO and FP-LAPW approaches are found to be 6.48 and 5.84 eV, respectively at Γ point of BZ leading to its direct band gap character. Our LCAO based computations give close agreement with experimental value of 7.9 eV. The DOS curves validate the dominance of O-2p states in the top valence band with a minor role of B-2p electrons. The conduction band region consists of dominant contribution of B-2p states.